The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14137913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 Nanoparticles on Performance and Emission Characteristics of Diesel Engine Fuelled with Diesel–Neem Biodiesel Blends

Abstract: Indagation in the sphere of nanoparticle utilisation has provided commendatory upshots in discrete areas of application varying from medicinal use to environmental degradation alleviation. This study incorporates alumina nanoparticles as additives to diesel and biodiesel blends. The prime objective of the present study was the scrutinisation of the denouement of Al2O3 nanoparticle incorporation in diesel–biodiesel blends on a diesel engine’s performance and emission characteristics. Test fuel samples were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…As a result, it is possible to create an appropriate regression equation that will offer a highly accurate and precise prediction of the Q i from the chosen combinations of the control factors. The non-symmetric bell-shaped histogram uses normal distribution for the analysis and gives the fit of the data available (Hasnain et al, 2023; Li et al, 2023; Thejas et al, 2022). The versus fits show that the residuals are randomly distributed having constant variance and the same has been in accordance with (Singh, Sharma, et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is possible to create an appropriate regression equation that will offer a highly accurate and precise prediction of the Q i from the chosen combinations of the control factors. The non-symmetric bell-shaped histogram uses normal distribution for the analysis and gives the fit of the data available (Hasnain et al, 2023; Li et al, 2023; Thejas et al, 2022). The versus fits show that the residuals are randomly distributed having constant variance and the same has been in accordance with (Singh, Sharma, et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To commence, the investigation encompasses the application of FT-IR spectroscopy to examine waste plastic oil. FT-IR is a unique technique for identifying specific chemical groups in waste plastic oil samples, including alcohol, hydroperoxide, carbonyl acid, ester, carboxylic acid, ketones, aldehyde, along with various stretching and bending vibrations (Hasnain et al, 2023; Li et al, 2023; Singh et al, 2021). The thorough chemical analysis presented herein offers an exhaustive insight into the constituents of waste plastic oil.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, using an ultrasonicator and a mechanically controlled conventional homogenizer, nanoparticles were combined with diary scum oil methyl ester (DiSOME) in the mass fraction range of 10 to 30 parts per million (ppm) in increments of 10 [109]. The effects of Al 2 O 3 NP on the ignition characteristics and engine outgas levels of a single cylinder, four-stroke, directinjection diesel engine operating in dual fuel mode with producer gas (PG) [112] have been studied in the following section of the work [113]. Engine testing revealed that Al2O3based NF and PG operation trials increased brake thermal efficiency by 11.5%, reduced smoke by 23.2%, and reduced hydrocarbon (HC) and carbon monoxide emissions by 18.2-21.4% (CO).…”
Section: Aluminum Oxidementioning
confidence: 99%
“…Based on the research, biodiesel greatly reduced the emission of CO 2 , CO, HCl, and NOx. Kaushik et al 33 have alumina nanoparticles, which were added into mixtures of biodiesel and diesel fuel. The primary goal of the current research were to carefully examine how the addition of Al 2 O 3 nanoparticles to diesel‐biodiesel blends affected the efficiency and pollution parameters of diesel engines.…”
Section: Review Of Literaturementioning
confidence: 99%